Production of Cinnamic and p-Hydroxycinnamic Acids in Engineered Microbes - Vargas-Tah, Alejandra; Gosset, Guillermo (Frontiers in Bioengineering and Biotechnology, 2015)
The aromatic compounds cinnamic and p-hydroxycinnamic acids are phenylpropanoids having applications as precursors for the synthesis of thermoplastics, flavoring, cosmetic and health products. These two aromatic acids can be obtained by chemical synthesis or extraction from plant tissues. However, both manufacturing processes have shortcomings such as the generation of toxic subproducts or a low concentration in plant material. Alternative production methods are being developed to enable the biotechnological production of cinnamic and p-hydroxycinnamic acids by genetically engineering various microbial hosts, including Escherichia coli, Saccharomyces cerevisiae, Pseudomonas putida and Streptomyces lividans. The natural capacity to synthesize these aromatic acids is not existent in these microbial species. Therefore, genetic modification have been performed that include the heterologous expression of genes encoding phenylalanine ammonia-lyase and tyrosine ammonia-lyase activities, which catalyze the conversion of L-phenylalanine and L-tyrosine to cinnamic acid and p-hydroxycinnamic acid, respectively. Additional host modifications include the metabolic engineering to increase carbon flow from central metabolism to the L-phenylalanine or L-tyrosine biosynthetic pathways. These strategies include the expression of feedback insensitive mutant versions of enzymes from the aromatic pathways, as well as genetic modifications to central carbon metabolism to increase biosynthetic availability of precursors phosphoenolpyruvate and erythrose-4-phosphate. These efforts have been complemented with strain optimization for the utilization of raw material, including various simple carbon sources, as well as sugar polymers and sugar mixtures derived from plant biomass. A systems biology approach to production strains characterization has been limited so far and should yield important data for future strain improvement.